Blended Learning to Improve the Physical Examination Ability of Nursing Students - Supriatin, Supriatin; Rithpho, Pratuma; Asiah, Asiah; Hikhmat, Rokhmatul (International Journal of Educational Qualitative Quantitative Research, 2022)
Coronavirus disease has an impact on the education sector. Educators use a combined learning method between face-to-face and online learning to break the chain of virus spread. One of the proper methods is blended learning with the help of information and communication technology to achieve learning objectives. This study aimed to determine the effectiveness of the blended learning method on the physical examination abilities of nursing students. This study uses a pre-experiment. The research location is in STIKes (College of Health Sciences), Cirebon, Indonesia, with a sample of 100 Nursing students. The technique uses purposive sampling and the N-Gain value analysis. The result shows a significant difference in the competence of the physical examination before and after getting the blended learning method. The blended learning method is proven effective in increasing the competence of the physical examination of nursing students. In addition, an exciting learning process through online and conventional media provides a high satisfaction value. Blended learning is one of the learning solutions in the new era of the COVID-19 pandemic to suppress the spread of COVID-19 and improve students' abilities.